(untitled) (Research, Society and Development, 2022)
Objective: To understand the factors related to men aged between 20 and 59 years not seeking basic health services in the city of Imperatriz - MA. Methodology: exploratory quantitative study that was developed through a semi-structured questionnaire with objective questions applied through the Forms platform. Results: 169 men answered the instrument, and of these, 86.39% were aged between 20 and 40 years, most were single 69.23%. Regarding the search for the primary care service for disease prevention or health promotion, 39.06% indicated that they only seek it when they feel a symptom, and 42.60% report that when they observe any sign or symptom, they look for it as a gateway in the health system to tertiary care to solve the problem. Conclusion: Based on the results obtained, it is clear that men are hesitant to seek health services. In this context, there is a need for the effective execution of public policies for this public in order to have a demand for primary care as a preventive form.